Management of grassland/savannas encroached by woody plants in South American Semiarid Chaco: Ecological restoration vs. African grasses introduction - Coria, Rubén Darío; Kunst, Carlos Roberto; Anriquez, Analía Liliana; Bravo, Sandra (Asociación Argentina de Ecología, 2023)
In Semiarid Chaco, two management approaches for woody plant-encroached grassland/savannas were evaluated: ecological restoration and the African grass introduction. An experiment with five treatments was carried out: 1) reference community (Ref_Eco; a grassland/savanna in good state, used as standard of comparison); 2) grassland/savanna encroached by woody plants (Woody_Encr; the woody state of grassland/savannas); 3) roller chopping of the encroached ecosystem, followed by grazing suppression and prescribed fire (Roll_Fire; aimed at inducing grassland/savanna ecological restoration); 4) roller chopping of the encroached ecosystem, with instantaneous seeding of Megathyrsus maximus cv. Gatton Panic and grazing suppression (Roll_Gatton Panic), and 5) roller chopping of the encroached ecosystem, with instantaneous seeding of Cenchrus ciliaris cv. Buffel Texas and grazing suppression (Roll_Buffel Texas). The last two treatments aimed to obtain new highly productive grassy states for ranching through the introduction of these African grasses. The results suggested that Ref_Eco (average herbaceous biomass [HERB]=7196.9 kg DM/ha) was dominated by shade intolerant and fire tolerant grasses, and it had good soil quality and good utilitarian range condition. Regarding Ref_Eco: a) in Woody_Encr (HERB=2192 kg DM/ha), the vegetation structure, plant composition and the utilitarian range condition were altered, but it still had good soil quality and abundant native grass populations; b) in Rol_Fire (HERB=6591.6 kg DM/ha), both the vegetation structure and good utilitarian range condition were restored, plant composition was not restored and the good soil quality was kept, and c) Roll_Gatton Panic and Roll_Buffel Texas (HERB=10972.1 and 7450.8 kg DM/ha, respectively) resulted in new grassy states integrated by native and exotic grasses with good utilitarian range condition and good soil quality. In this study case, the ecological restoration of the encroached ecosystems would be both ecologically and productively viable. So, probably the introduction of African grasses to improve ranching was not necessary.